2022
DOI: 10.3389/fpls.2022.836244
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circadian Rhythms in Major Plant Metabolic and Signaling Pathways

Abstract: Plants require an endogenous regulatory network and mechanism to cope with diurnal environmental changes and compensate for their sessile nature. Plants use the circadian clock to anticipate diurnal changes. Circadian rhythm predicts a 24-h cycle with 16 h of light and 8 h of darkness in response to abiotic and biotic factors as well as the appropriate temperature. For a plant’s fitness, proper growth, and development, these rhythms synchronize the diurnal photoperiodic changes. Input pathway, central oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 121 publications
2
27
0
2
Order By: Relevance
“…Circadian rhythm of plants controls the molecular and cellular expression patterns to regulate better and mediate the light and dark periods, which in turn gives a fitness benefit to the plant ( Venkat and Muneer, 2022 ). A. heterophyllus has two positively selected genes, PRR7 (pseudo-response regulator 7) and CSNK2A (Casein kinase II subunit alpha), which regulate plant circadian rhythms (see Figure 8C ).…”
Section: Resultsmentioning
confidence: 99%
“…Circadian rhythm of plants controls the molecular and cellular expression patterns to regulate better and mediate the light and dark periods, which in turn gives a fitness benefit to the plant ( Venkat and Muneer, 2022 ). A. heterophyllus has two positively selected genes, PRR7 (pseudo-response regulator 7) and CSNK2A (Casein kinase II subunit alpha), which regulate plant circadian rhythms (see Figure 8C ).…”
Section: Resultsmentioning
confidence: 99%
“…Circadian rhythm of plants controls the molecular and cellular expression patterns to regulate better and mediate the light and dark periods, which in turn gives a fitness benefit to the plant (Venkat and Muneer, 2022). A. heterophyllus has two positively selected genes, PRR7 (pseudo-response regulator 7) and CSNK2A (Casein kinase II subunit alpha), which regulate plant circadian rhythms.…”
Section: Resultsmentioning
confidence: 99%
“…Pattern recognition receptor (PRR) EIX receptor 1/2 was positively selected in both A. heterophyllus and A. altilis. Other than this PRR, A. altilis showed positive selection in multiple different genes involved in plant-pathogen interactions, like CNGC (Cyclic nucleotide-gated channel), a transmembrane protein providing fungal response PTI1 (pto-interacting protein 1), BAK1 and KCS (3-ketoacyl-coA synthase) involved in bacterial defence responses.Circadian rhythm in the plant (see Figure8C): Circadian rhythm of plants controls the molecular and cellular expression patterns to regulate better and mediate the light and dark periods, which in turn gives a fitness benefit to the plant(Venkat and Muneer, 2022). A. heterophyllus has two positively selected genes, PRR7 (pseudo-response regulator 7) and CSNK2A (Casein kinase II subunit alpha), which regulate plant circadian rhythms.…”
mentioning
confidence: 99%
“…By utilizing circadian rhythm datasets, we found that GmASMT27 showed circadian clock oscillation ( Figure 3 ), a characteristics feature of LCL1, involved in maintaining circadian rhythmicity in plants ( Wang et al, 2020 ). Recent reports also demonstrated the importance of circadian rhythm in various physiological processes, metabolic pathways, developmental and degenerative processes ( Venkat and Muneer, 2022 ).…”
Section: Discussionmentioning
confidence: 99%